ANALYZING CONSUMER FINANCING RECEIVABLES, NON-PERFORMING FINANCING, DEBT RATIO, AND PROFITABILITY OF PT.BFI FINANCE INDONESIA, TBK. (PERIOD 2006-2016) - Ferdinand Butar-butar; Jessica Herlina Laihad (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2018)
Multi-finance industry has seen some deterioration in their profitability level in the past 2 years. Profitability of a multi-finance company, which usually is being represented by ROA and ROE, is dependent on several factors, which include its consumer financing receivables, non-performing financing, and debt ratios. Thus, the aim of this research is to analyze consumer financing receivables, non-performing financing, debt ratio and profitability of BFI Finance Indonesia, a multi finance company.The data in this research was collected using secondary data, which includes related literature to obtain related theory and analysis method, and related figures from BFI Finance Indonesia’s Annual Financial Statements that has been published during 2006-2016 period. The result shows BFI Finance Indonesia is a healthy multi finance company with increasing trend of customer financing receivables and debt ratios, plus a decreasing trend non-performing financing ratio. This ultimately result in an positive profitability which is shown in increasing ROA and ROE level through the research period.